88 A comparison of psychomotor skills in novice surgeons using a diy laparoscopic simulator and a commercially built standard box trainer. (17th November 2016) - Varzgalis, M; Choi, PJK; Koh, T; Byrne, D; Reid McDermott, B; De Freitas, S; Kelly, M; Carter, M; Kerin, MJ
Abstract : Introduction: The use of laparoscopic simulators in surgery is commonplace. Improvements in simulator technology has been accelerated by augmentation with virtual reality and haptic feedback. Laparoscopic simulators at the upper end of the technology spectrum may cost in excess of 100, 000 euro and are not accessible by novice surgical trainees. Regular access to simulators is important in the acquisition of psychomotor skills and is associated with improved performance in the operating theatre. Aim: To compare the performance of a commercially available box trainer with a DIY version in the acquisition of basic laparoscopic skills in novice surgeons. Methods: Medical students with an interest in surger (n = 19) were recruited and allocated to two groups. Each group had 6 non-consecutive hours practice on either the DIY (group B) or commercial box trainer (group A) in basic transfer and hand–eye coordination skills. Their accuracy and speed of completion of 3 validated laparoscopic skills was measured 2 weeks after the practice sessions. Performance was recorded by blinded assessors and analysed for comparison. Results: Conclusion: The psychomotor skills of the group trained using the DIY simulator are comparable with those of the standard box trainer group. The cost difference between the 2 simulators is over 1, 700 euro and the DIY version is within the budget of every medical school and surgical training site. These cost effective simulators can provide the novice surgeon with opportunities for repetitive practice and skills improvement, ultimately translating to improved surgical performance.